Nurses' experiences of caring for patients with different cultures in Mashhad, Iran - Rana Amiri; Abbas Heydari (Wolters Kluwer Medknow Publications, 2017)
Background: Mashhad is a center of diverse cultures, where many local and foreign cultures live together in its context. One of the main needs of a society with cultural diversity is transcultural care of patients. Hence, the present study took the first step for care of culturally diversified and minority patients in Mashhad. This research has been conducted to explore the nurses' experience of caring from patients with different cultures. Materials and Methods: This study is a qualitative research using phenomenological hermeneutics approach. The participations include nurses who have been working 5 or less than 5 years in the hospitals affiliated to Medical University of Mashhad. They were selected using purposeful sampling method. For data collection, semi-structured, in-depth interview was used. For data analysis, interpretation method was used. The interviews continued until saturation of data was obtained. Results: Data analysis resulted in extraction of 4 themes including ethnocentrism, contradicting perceptions of care, it is not our fault, and lack of cultural knowledge. Conclusions: The experience of nurses in taking care of patients with other cultures showed that minorities and small cultures have been neglected in Mashhad and hospitalization of such people in hospitals and other clinics is not specific. We recommend that an educational curriculum about transcultural care should be added to nursing courses. Also, necessary equipment and facilities should be considered and prepared for culturally different patients in hospitals.